Inflation thresholds and inattention - Anat Bracha; Jenny Tang (Federal Reserve Bank of Boston, 2019)
Inflation expectations are key to economic activity, and in the current economic climate of a heated labor market, they are central to the policy debate. At the same time, a growing literature on inattention suggests that individuals, and therefore individual behavior, may not be sensitive to changes in inflation when it is low. This paper explores evidence of such inattention by constructing three different measures based on the University of Michigan's Survey of Consumers 1-year ahead inflation expectations. Exploring inflation thresholds of 2, 3, and 4 percent, our findings are consistent with the inattention hypothesis.
Keywords: D83; D84; E31; E71; 330; inattention; inflation expectations; Phillips curve